Adherence to precautions for preventing the transmission of microorganisms in primary health care: a qualitative study - Maroldi, Michely Aparecida Cardoso; Felix, Adriana Maria da Silva; Dias, Ana Angélica Lima; Kawagoe, Julia Yaeko; Padoveze, Maria Clara; Ferreira, Sílvia Alice; Zem-Mascarenhas, Sílvia Helena; Timmons, Stephen; Figueiredo, Rosely Moralez (BioMed Central, 2017)
Background